The Employer’s Legal Obligations Toward Workers’ Rights Arising from Termination of Employment (A Comparative Study between Indonesia and Germany): Kewajiban Hukum Pengusaha Terhadap Hak Pekerja Akibat Pemutusan Hubungan Kerja (Studi Komparatif Indonesia dan Jerman) - Lie, Gunardi; Sitorus, Lena Mariana Br (Indonesian Journal of Law and Economics Review, 2025)
General Background: Termination of employment remains a critical issue in labor law due to its social, economic, and legal consequences for workers. Specific Background: In Indonesia, despite comprehensive regulation under the Manpower Law and Job Creation Law, unilateral termination continues to occur, often without due process or fulfillment of workers’ entitlements, as illustrated in the case of PT X. Knowledge Gap: However, comparative studies examining the adequacy of Indonesian protections in relation to countries with stronger welfare-oriented systems, such as Germany, remain limited. Aims: This study aims to analyze the legal obligations of employers regarding workers’ rights arising from unilateral termination and to compare regulatory frameworks between Indonesia and Germany. Results: Findings show that Indonesia provides normative protection but faces weak enforcement, inconsistent application of compensation rules, and limited procedural safeguards, whereas Germany—through the Kündigungsschutzgesetz—implements stricter termination requirements, mandatory works-council consultation, and comprehensive social security support. Novelty: This study offers a detailed doctrinal and case-based comparison highlighting structural gaps in Indonesian law using a welfare-state benchmark. Implications: Strengthening enforcement mechanisms, enhancing oversight, and integrating social security-based protections could significantly improve Indonesia’s system for safeguarding workers against unjust termination. Highlights: Highlights the gap between normative regulation and practical enforcement in Indonesia. Emphasizes Germany’s stronger procedural and welfare-based safeguards for workers. Identifies the need for Indonesia to strengthen legal implementation and social protection mechanisms. Keywords: Termination of Employment, Legal Protection, Workers’ Rights, Labor Law